Kinetic study of the biodegradation of acephate by indigenous soil bacterial isolates in the presence of humic acid and metal ions - Singh, Simranjeet; Kumar, Vijay; Singla, Sourav; Sharma, Minaxi; Singh, Dhananjaya P.; Prasad, Ram; Thakur, Vijay Kumar; Singh, Joginder (MDPI, 2020)
Many bacteria have the potential to use specific pesticides as a source of carbon, phosphorous, nitrogen and sulphur. Acephate degradation by microbes is considered to be a safe and effective method. The overall aim of the present study was to identify acephate biodegrading microorganisms and to investigate the degradation rates of acephate under the stress of humic acid and most common metal ions Fe(III) and copper Cu(II). Pseudomonas azotoformanss strain ACP1, Pseudomonas aeruginosa strain ACP2, and Pseudomonas putida ACP3 were isolated from acephate contaminated soils. Acephate of concentration 100 ppm was incubated with separate strain inoculums and periodic samples were drawn for UV—visible, FTIR (Fourier-transform infrared spectroscopy) and MS (Mass Spectrometry) analysis. Methamidophos, S-methyl O-hydrogen phosphorothioamidate, phosphenothioic S-acid, and phosphenamide were the major metabolites formed during the degradation of acephate. The rate of degradation was applied using pseudo-first-order kinetics to calculate the half-life (t1/2) values, which were 14.33–16.72 d−1 (strain(s) + acephate), 18.81–21.50 d−1 (strain(s) + acephate + Cu(II)), 20.06 –23.15 d−1 (strain(s) + acephate + Fe(II)), and 15.05–17.70 d−1 (strains + acephate + HA). The biodegradation efficiency of the three bacterial strains can be ordered as P. aeruginosa > P. putida > P. azotoformans. The present study illustrated the decomposition mechanism of acephate under different conditions, and the same may be applied to the removal of other xenobiotic compounds
Keywords: toxicity; Pseudomonas; metal stress; humic acid; acephate